HHV-8-Associated Multicentric Castleman Disease, a Diagnostic Challenge in a Patient With Acquired Immunodeficiency Syndrome and Fever. (May 2022) - Dunn, Robert; Jariwal, Roopam; Venter, Frederick; Mishra, Shikha; Bhandohal, Janpreet; Cobos, Everado; Heidari, Arash
Patients with acquired immunodeficiency syndrome (AIDS) are at an increased susceptibility to pathogens and associated malignancies which can present with a unique constellation of symptoms. In this article, we describe a case of Castleman disease in a patient with AIDS, nonadherent with antiretroviral therapy (ART), who presented with fevers, constant abdominal pain, nausea, and vomiting. After an extensive work up, a lymph node biopsy confirmed a diagnosis of human herpesvirus-8 (HHV-8)-associated multicentric Castleman disease. Patients presenting with AIDS and fever have broad differential diagnoses; therefore, reaching a diagnosis as rare as Castleman disease can be challenging. HHV-8 has a propensity to CD20 positive B cells, which allows rituximab to be an effect treatment.